1980
DOI: 10.1111/j.1399-0004.1980.tb00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity of congenital glaucoma

Abstract: Analysis of 126 families comprising 205 patients with congenital glaucoma demonstrates that in Gypsies this disease follows the pattern of autosomal recessive inheritance with complete penetrance, while in the non‐Gypsy population, its mode of inheritance is most probably multifactorial. In Gypsy patients with congenital glaucoma, the eyes are always bilaterally affected, the onset of the disease is in the prenatal period, and its course is rather severe. The population frequency of the disease is extremely hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…In the present study, in line with previous studies, the mean prevalence and incidence of PCG were higher in males than in females. The 4.73 versus 3.47 ratio of males to females for the prevalence of PCG in this study is smaller than the 2:1 ratio reported for an Australian population 16 but similar to that of 1.55:1, reported by Gencik et al 17 The incidence of PCG also showed a slight male predominance in our study (1.83 vs. 1.36). Similarly, the Indian study on 275 patients with childhood glaucoma, noted earlier, had a high proportion of males (58.9%: 162 males vs. 113 females).…”
Section: Discussionsupporting
confidence: 75%
“…In the present study, in line with previous studies, the mean prevalence and incidence of PCG were higher in males than in females. The 4.73 versus 3.47 ratio of males to females for the prevalence of PCG in this study is smaller than the 2:1 ratio reported for an Australian population 16 but similar to that of 1.55:1, reported by Gencik et al 17 The incidence of PCG also showed a slight male predominance in our study (1.83 vs. 1.36). Similarly, the Indian study on 275 patients with childhood glaucoma, noted earlier, had a high proportion of males (58.9%: 162 males vs. 113 females).…”
Section: Discussionsupporting
confidence: 75%
“…21,22 Nonetheless, the genetic counsellor must estimate transmission risks and is unlikely to entertain non-Mendelian transmission frequencies. 23 Corroborating Genčík et al's work, 24 relatively few of our probands were found to have a PIG affected sibling. The majority of our PIG cases seem to be sporadic.…”
Section: Discussionsupporting
confidence: 51%
“…Our finding of 17 carriers in a sample of 158 healthy Roms (10.8%), assuming Hardy-Weinberg equilibrium, would imply an allele frequency of 5.7% and a homozygote frequency of 0.3% (1:308), which is four times more than the estimated incidence of PCG in Slovak Roms by Genčik et al 15. This shows that the E387K mutation is indeed widespread in the Rom ethnic group, and provides an explanation for the occurrence of several cases of parent-child (“pseudodominant”) transmission of the disease reported previously,25 27 as well as for the occurrence of large kinships, containing sometimes >30 affected members in several generations 28. The difference between the original estimate of the mutation frequency15and that reported here is significant (p<0.01), and may be the result of the randomly increased incidence of the mutation in the communities from which our sample originates.…”
Section: Discussionmentioning
confidence: 59%
“…Genčik et al 25performed the first clinical and genetic study of PCG in the Slovak Roms and noticed that, in this population, the disease was clinically much more uniform, its course was more severe, and its prognosis worse than in the non-Rom patients. In Roms with PCG, the eyes are always bilaterally affected (while in the non-Roms this is the case in only <75%), the intraocular pressure is almost always >29 mm Hg (while in non-Roms, it is almost always <24 mm Hg), the disease can be always diagnosed at birth or within the first months of life (while in non-Roms, only one third of cases were diagnosed at birth, and less than 90% by the 12th month of life), and the response to surgical intervention as well as to other forms of treatment is much less favourable compared with that in non-Roms.…”
Section: Discussionmentioning
confidence: 99%